11institutetext: École polytechnique and INRIA
LIX, École polytechnique, 91128 Palaiseau cedex, France
11email: Gilles.Dowek@polytechnique.fr
22institutetext: Université Paris 7,
PPS, 175 Rue du Chevaleret, 75013 Paris, France
22email: Alexandre.Miquel@pps.jussieu.fr

Relative normalization

Gilles Dowek 11    Alexandre Miquel 22

Gödel’s second incompleteness theorem forbids to prove, in a given theory 𝒰𝒰\mathcal{U}, the consistency of many theories—in particular, of the theory 𝒰𝒰\mathcal{U} itself—as well as it forbids to prove the normalization property for these theories, since this property implies their consistency. When we cannot prove in a theory 𝒰𝒰\mathcal{U} the consistency of a theory 𝒯𝒯\mathcal{T}, we can try to prove a relative consistency theorem, that is, a theorem of the form:

If 𝒰𝒰\mathcal{U} is consistent then 𝒯𝒯\mathcal{T} is consistent.

Following the same spirit, we show in this paper how to prove relative normalization theorems, that is, theorems of the form:

If 𝒰𝒰\mathcal{U} is 111-consistent, then 𝒯𝒯\mathcal{T} has the normalization property.

1 An abstract consistency result

To prove that a theory 𝒯𝒯\mathcal{T} is consistent provided the theory 𝒰𝒰\mathcal{U} is, we usually assume given a model of 𝒰𝒰\mathcal{U} and we build a model of 𝒯𝒯\mathcal{T}. When the domain of the model of 𝒯𝒯\mathcal{T} is a subset of the domain of the model of 𝒰𝒰\mathcal{U}—which is called an internal model—we can however proceed in a slightly different way: instead of mapping a formula A𝐴A of 𝒯𝒯\mathcal{T} to a truth value Aϕ\llbracket A\rrbracket_{\phi} (depending on an assignment ϕitalic-ϕ\phi) we can translate it into a formula Asuperscript𝐴A^{*} of 𝒰𝒰\mathcal{U} that expresses that the truth value associated to A𝐴A is 111. And instead of proving that 𝒯Aproves𝒯𝐴\mathcal{T}\vdash A entails Aϕ=1\llbracket A\rrbracket_{\phi}=1, we prove that 𝒯Aproves𝒯𝐴\mathcal{T}\vdash A entails 𝒰Aproves𝒰superscript𝐴\mathcal{U}\vdash A^{*}. Finally, if superscriptbottom\bot^{*} is bottom\bot (or any equivalent formula in 𝒰𝒰\mathcal{U}) and if the theory 𝒰𝒰\mathcal{U} is consistent, then the theory 𝒯𝒯\mathcal{T} is consistent too.

Unlike the method based on model extrusion, the method by which formulæ of 𝒯𝒯\mathcal{T} are directly translated as formulæ of 𝒰𝒰\mathcal{U} does not require to take care of the free variables of A𝐴A with an assignment: free variables of A𝐴A just remain free variables of Asuperscript𝐴A^{*}, after being possibly renamed.

This way of proving the consistency of 𝒯𝒯\mathcal{T} is quite different from proving in 𝒰𝒰\mathcal{U} the existence of a model of 𝒯𝒯\mathcal{T}, as we do not need to define a domain of interpretation: all the universe of discourse of the theory 𝒰𝒰\mathcal{U}—or part of it—can serve as domain. Thus this method can be applied also in cases where the existence of a model of 𝒯𝒯\mathcal{T} can not be proved in 𝒰𝒰\mathcal{U}.

Definition 1

— An interpretation of a theory 𝒯𝒯\mathcal{T} in a theory 𝒰𝒰\mathcal{U} is given by

  • a function which maps each sort s𝑠s of 𝒯𝒯\mathcal{T} to a sort ssubscript𝑠s_{*} of 𝒰𝒰\mathcal{U} with a relativization predicate s(x)superscript𝑠𝑥s^{*}(x) in 𝒰𝒰\mathcal{U} (with x𝑥x of sort ssubscript𝑠s_{*}), such that 𝒰xs(x)proves𝒰𝑥superscript𝑠𝑥\mathcal{U}\vdash\exists x~{}s^{*}(x).

  • a function which maps each variable x𝑥x of sort s𝑠s in 𝒯𝒯\mathcal{T} to a variable xsuperscript𝑥x^{*} of sort ssubscript𝑠s_{*} in 𝒰𝒰\mathcal{U};

  • a function which maps each formula A𝐴A of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} in 𝒯𝒯\mathcal{T} to a formula Asuperscript𝐴A^{*} of 𝒰𝒰\mathcal{U} whose free variables occur among the variables x1,,xnsuperscriptsubscript𝑥1superscriptsubscript𝑥𝑛x_{1}^{*},\ldots,x_{n}^{*}

for which we require that

  1. 1.

    for all sorts s𝑠s of 𝒯𝒯\mathcal{T} we have 𝒰xs(x)proves𝒰𝑥superscript𝑠𝑥\mathcal{U}\vdash\exists x~{}s^{*}(x);

  2. 2.

    for all formulæ A𝐴A and B𝐵B of 𝒯𝒯\mathcal{T} whose free variables occur among the variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} in 𝒯𝒯\mathcal{T} we have:

    UUUs1(x1)sn(xn)((AB)(AB))Us1(x1)sn(xn)((AB)(AB))Us1(x1)sn(xn)((AB)(AB))Us1(x1)sn1(xn1)((xnA)xn(sn(xn)A))Us1(x1)sn1(xn1)((xnA)xn(sn(xn)A))\begin{array}[]{l}U\vdash\bot^{*}\Leftrightarrow\bot\\ U\vdash\top^{*}\Leftrightarrow\top\\ U\vdash s_{1}^{*}(x^{*}_{1})\land\cdots\land s_{n}^{*}(x^{*}_{n})~{}\Rightarrow~{}\bigl{(}(A\land B)^{*}\Leftrightarrow(A^{*}\land B^{*})\bigr{)}\\ U\vdash s_{1}^{*}(x^{*}_{1})\land\cdots\land s_{n}^{*}(x^{*}_{n})~{}\Rightarrow~{}\bigl{(}(A\lor B)^{*}\Leftrightarrow(A^{*}\lor B^{*})\bigr{)}\\ U\vdash s_{1}^{*}(x^{*}_{1})\land\cdots\land s_{n}^{*}(x^{*}_{n})~{}\Rightarrow~{}\bigl{(}(A\Rightarrow B)^{*}\Leftrightarrow(A^{*}\Rightarrow B^{*})\bigr{)}\\ U\vdash s_{1}^{*}(x^{*}_{1})\land\cdots\land s_{n-1}^{*}(x^{*}_{n-1})~{}\Rightarrow~{}\bigl{(}(\forall x_{n}\,A)^{*}\Leftrightarrow\forall x^{*}_{n}\,(s_{n}^{*}(x^{*}_{n})\Rightarrow A^{*})\bigr{)}\\ U\vdash s_{1}^{*}(x^{*}_{1})\land\cdots\land s_{n-1}^{*}(x^{*}_{n-1})~{}\Rightarrow~{}\bigl{(}(\exists x_{n}\,A)^{*}\Leftrightarrow\exists x^{*}_{n}\,(s_{n}^{*}(x^{*}_{n})\land A^{*})\bigr{)}\\ \end{array}
  3. 3.

    for all axioms A𝐴A of 𝒯𝒯\mathcal{T} we have: 𝒰Aproves𝒰superscript𝐴\mathcal{U}\vdash A^{*} (assuming that the axioms of 𝒯𝒯\mathcal{T} are closed formulæ).

A simple way to define the underlying translation AAmaps-to𝐴superscript𝐴A\mapsto A^{*} of such an interpretation is to define it structurally on formulæ, by first defining the formula Asuperscript𝐴A^{*} for each atomic formula A𝐴A of 𝒯𝒯\mathcal{T}, and then by extending the definition inductively to all formulæ using the equations

(AB)(AB)(AB)(AB)(xA)x(s(x)A)(AB)(AB)(xA)x(s(x)A)superscript𝐴𝐵superscript𝐴superscript𝐵superscripttoptopsuperscriptbottombottomsuperscript𝐴𝐵superscript𝐴superscript𝐵superscriptfor-all𝑥𝐴for-allsuperscript𝑥superscript𝑠superscript𝑥superscript𝐴superscript𝐴𝐵superscript𝐴superscript𝐵superscript𝑥𝐴superscript𝑥superscript𝑠superscript𝑥superscript𝐴\begin{array}[]{r@{~~}c@{~~}l@{\qquad\qquad}r@{~~}c@{~~}l}(A\Rightarrow B)^{*}~{}~{}&\equiv\hfil~{}~{}&(A^{*}\Rightarrow B^{*})&\lx@intercol\top^{*}~{}\equiv~{}\top\qquad\quad\bot^{*}~{}\equiv~{}\bot\hfil\lx@intercol\\ (A\land B)^{*}~{}~{}&\equiv\hfil~{}~{}&(A^{*}\land B^{*})&(\forall x\,A)^{*}~{}~{}&\equiv\hfil~{}~{}&\forall x^{*}\,(s^{*}(x^{*})\Rightarrow A^{*})\\ (A\lor B)^{*}~{}~{}&\equiv\hfil~{}~{}&(A^{*}\lor B^{*})&(\exists x\,A)^{*}~{}~{}&\equiv\hfil~{}~{}&\exists x^{*}\,(s^{*}(x^{*})\land A^{*})\\ \end{array}

(assuming that s𝑠s is the sort of the variable x𝑥x). In this case, the conditions required in item 1 of the definition above come for free, but the soundness of all the axioms of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U} still has to be checked separately.

Notice that the definition of the notion of interpretation (of a theory into another one) does not say anything about the translation of terms. The reason is that in some cases, it is desirable to interpret a theory with a rich term language (such as Peano arithmetic) into a theory with a poor one (such as set theory), so that we can not expect that terms of 𝒯𝒯\mathcal{T} are always interpreted as terms of 𝒰𝒰\mathcal{U}.

However, interpretations are usually structural on terms too, which means that they come with a translation ttmaps-to𝑡superscript𝑡t\mapsto t^{*} on terms such that

  • for all terms t𝑡t of sort s𝑠s whose free variables occur among the variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} in the theory 𝒯𝒯\mathcal{T}, one has:

    𝒰s1(x1)sn(xn)s(t)proves𝒰subscriptsuperscript𝑠1subscriptsuperscript𝑥1subscriptsuperscript𝑠𝑛subscriptsuperscript𝑥𝑛superscript𝑠superscript𝑡\mathcal{U}\vdash s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})~{}\Rightarrow~{}s^{*}(t^{*})
  • for all well-formed terms of 𝒯𝒯\mathcal{T} of the form f(t1,,tn)𝑓subscript𝑡1subscript𝑡𝑛f(t_{1},\ldots,t_{n}) (where f𝑓f is an arbitrary function symbol of 𝒯𝒯\mathcal{T}), one has:111This condition says that each function symbol f𝑓f of 𝒯𝒯\mathcal{T} is translated as a macro in 𝒰𝒰\mathcal{U}.

    (f(t1,,tn))=(f(x1,,xn)){x1:=t1;;xn:=tn}.superscript𝑓subscript𝑡1subscript𝑡𝑛superscript𝑓subscript𝑥1subscript𝑥𝑛formulae-sequenceassignsubscriptsuperscript𝑥1subscriptsuperscript𝑡1assignsubscriptsuperscript𝑥𝑛subscriptsuperscript𝑡𝑛(f(t_{1},\ldots,t_{n}))^{*}=(f(x_{1},\ldots,x_{n}))^{*}\{x^{*}_{1}:=t^{*}_{1};\ldots;x^{*}_{n}:=t^{*}_{n}\}\,.

The main interest of the notion of interpretation (in the sense of Def. 1) is that it provides a way to translate each theorem of 𝒯𝒯\mathcal{T} into a theorem of 𝒰𝒰\mathcal{U}:

Proposition 1

— Given an interpretation * of a theory 𝒯𝒯\mathcal{T} in a theory 𝒰𝒰\mathcal{U} and a formula A𝐴A of 𝒯𝒯\mathcal{T} whose free variables occur among the variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} in 𝒯𝒯\mathcal{T}, if 𝒯Aproves𝒯𝐴\mathcal{T}\vdash A then

𝒰s1(x1)sn(xn)Aproves𝒰superscriptsubscript𝑠1subscriptsuperscript𝑥1superscriptsubscript𝑠𝑛subscriptsuperscript𝑥𝑛superscript𝐴\mathcal{U}\vdash s_{1}^{*}(x^{*}_{1})\land...\land s_{n}^{*}(x^{*}_{n})\Rightarrow A^{*}
Proof

By induction on the structure of the proof of 𝒯Aproves𝒯𝐴\mathcal{T}\vdash A.

Theorem 1.1

— If the theory 𝒯𝒯\mathcal{T} has an interpretation in 𝒰𝒰\mathcal{U}, and if the theory 𝒰𝒰\mathcal{U} is consistent, then 𝒯𝒯\mathcal{T} is consistent too.

Proof

Assume 𝒯proves𝒯bottom\mathcal{T}\vdash\bot. From Prop. 1 we get 𝒰proves𝒰superscriptbottom\mathcal{U}\vdash\bot^{*} and thus 𝒰proves𝒰bottom\mathcal{U}\vdash\bot using the equivalence 𝒰\mathcal{U}\vdash\bot^{*}\Leftrightarrow\bot.∎

Notice that this way of proving the consistency of a theory directly extends to intuitionistic logic.

2 Normalization

2.1 Deduction modulo

We want to be able to speak abstractly of the normalization of proofs in an arbitrary theory 𝒯𝒯\mathcal{T} and also to be able to deduce some corollaries from the fact that 𝒯𝒯\mathcal{T} has the normalization property, in particular, the consistency of 𝒯𝒯\mathcal{T}, the disjunction and the witness property for constructive proofs, etc. It is well-known that predicate logic is not a appropriate for defining such a notion of normalization as each axiomatic theory 𝒯𝒯\mathcal{T} requires a specific notion of reduction. Thus we use an extension of predicate logic called Deduction modulo [1].

In Deduction modulo, a theory is formed is formed with a set of axioms ΓΓ\Gamma and a congruence \equiv defined on formulæ. Then, the deduction rules take this congruence into account. For instance, the modus ponens is not stated as usual

ABABinfer𝐵𝐴𝐵𝐴B\lx@proof@logical@and A\Rightarrow BA

as the first premise need not be exactly AB𝐴𝐵A\Rightarrow B but may be only congruent to this formula, hence it is stated

CAifCABBinfer𝐵𝐶𝐴B\lx@proof@logical@and CA

All the rules of natural deduction may be stated in a similar way. Many theories, such as arithmetic, simple type theory and set theory can be expressed with a congruence and no axioms.

Replacing axioms by a congruence changes the structure of proofs and in particular some theories may have the normalization property when expressed with axioms and not when expressed with a congruence. In counterpart, when theory formed with a congruence and no axioms has the normalization property, then we can deduce that it is consistent, constructive proofs have the disjunction and the witness property, various proof search methods are complete, etc.

2.2 Pre-models

A theory in Deduction modulo has the normalization property if it has what we call a pre-model [2]. A pre-model is a many-valued model whose truth values are reducibility candidates, that is, particular sets of strongly normalizable proof-terms whose definition is given below.

Definition 2 (Proof-term)

Proof-terms are inductively defined as follows:

π::=α(Axiom)|λαπ|(ππ)(-intro,-elim)|π,π|𝑓𝑠𝑡(π)|𝑠𝑛𝑑(π)(-intro,-elim1,2)|i(π)|j(π)|(δπ1απ2βπ3)(-intro1,2,-elim)|I(-intro)|(δπ)(-elim)|λxπ|(πt)(-intro,-elim)|t,π|(δπxαπ)(-intro,-elim)\begin{array}[]{r@{~~}r@{~~}l@{\qquad}l}\pi~{}~{}&::=~{}~{}&\alpha&(\text{Axiom})\\ ~{}~{}&|~{}~{}&\lambda\alpha~{}\pi\quad|\quad(\pi~{}\pi^{\prime})&({\Rightarrow}\text{-intro},~{}{\Rightarrow}\text{-elim})\\ ~{}~{}&|~{}~{}&\langle\pi,\pi^{\prime}\rangle\quad|\quad\mathit{fst}(\pi)\quad|\quad\mathit{snd}(\pi)&({\land}\text{-intro},~{}{\land}\text{-elim}_{1,2})\\ ~{}~{}&|~{}~{}&i(\pi)\quad|\quad j(\pi)\quad|\quad(\delta~{}\pi_{1}~{}\alpha\pi_{2}~{}\beta\pi_{3})&({\lor}\text{-intro}_{1,2},~{}{\lor}\text{-elim})\\ ~{}~{}&|~{}~{}&I&({\top}\text{-intro})\\ ~{}~{}&|~{}~{}&(\delta_{\bot}~{}\pi)&({\bot}\text{-elim})\\ ~{}~{}&|~{}~{}&\lambda x~{}\pi\quad|\quad(\pi~{}t)&({\forall}\text{-intro},~{}{\forall}\text{-elim})\\ ~{}~{}&|~{}~{}&\langle t,\pi\rangle\quad|\quad(\delta_{\exists}~{}\pi~{}x\alpha\pi^{\prime})&({\exists}\text{-intro},~{}{\exists}\text{-elim})\\ \end{array}

Each proof-term constructor corresponds to an inference rule of intuitionistic natural deduction (see above). A proof-term built using a constructor that corresponds to an introduction rule—that is, a proof-term of the form λαπ𝜆𝛼𝜋\lambda\alpha~{}\pi, π,π𝜋superscript𝜋\langle\pi,\pi^{\prime}\rangle, i(π)𝑖𝜋i(\pi), j(π)𝑗𝜋j(\pi), I𝐼I, λxπ𝜆𝑥𝜋\lambda x~{}\pi or t,π𝑡𝜋\langle t,\pi\rangle—is called an introduction. Similarly, a proof-term built using a constructor that corresponds to an elimination rule—that is, a proof-term of the form (ππ)𝜋superscript𝜋(\pi~{}\pi^{\prime}), 𝑓𝑠𝑡(π)𝑓𝑠𝑡𝜋\mathit{fst}(\pi), 𝑠𝑛𝑑(π)𝑠𝑛𝑑𝜋\mathit{snd}(\pi), (δπ1απ2βπ3)𝛿subscript𝜋1𝛼subscript𝜋2𝛽subscript𝜋3(\delta~{}\pi_{1}~{}\alpha\pi_{2}~{}\beta\pi_{3}), (δπ)subscript𝛿bottom𝜋(\delta_{\bot}~{}\pi), (πt)𝜋𝑡(\pi~{}t) or (δπxαπ)subscript𝛿𝜋𝑥𝛼superscript𝜋(\delta_{\exists}~{}\pi~{}x\alpha\pi^{\prime})—is called an elimination.

Definition 3 (Reduction)

Reduction on proof-terms is defined by the following rules that eliminate cuts step by step.

(λαπ1π2)π1(απ2)𝑓𝑠𝑡(π1,π2)π1𝑠𝑛𝑑(π1,π2)π2(δi(π1)απ2βπ3)π2(απ1)(δj(π1)απ2βπ3)π3(βπ1)(λxπt)π(xt)(δt,π1αxπ2)π2(xt,απ1)𝜆𝛼subscript𝜋1subscript𝜋2subscript𝜋1𝛼subscript𝜋2𝑓𝑠𝑡subscript𝜋1subscript𝜋2subscript𝜋1𝑠𝑛𝑑subscript𝜋1subscript𝜋2subscript𝜋2𝛿𝑖subscript𝜋1𝛼subscript𝜋2𝛽subscript𝜋3subscript𝜋2𝛼subscript𝜋1𝛿𝑗subscript𝜋1𝛼subscript𝜋2𝛽subscript𝜋3subscript𝜋3𝛽subscript𝜋1𝜆𝑥𝜋𝑡𝜋𝑥𝑡subscript𝛿𝑡subscript𝜋1𝛼𝑥subscript𝜋2subscript𝜋2formulae-sequence𝑥𝑡𝛼subscript𝜋1\begin{array}[]{r@{\quad}c@{\quad}l}(\lambda\alpha~{}\pi_{1}~{}\pi_{2})&\triangleright&\pi_{1}(\alpha\leftarrow\pi_{2})\\ \mathit{fst}(\langle\pi_{1},\pi_{2}\rangle)&\triangleright&\pi_{1}\\ \mathit{snd}(\langle\pi_{1},\pi_{2}\rangle)&\triangleright&\pi_{2}\\ (\delta~{}i(\pi_{1})~{}\alpha\pi_{2}~{}\beta\pi_{3})&\triangleright&\pi_{2}(\alpha\leftarrow\pi_{1})\\ (\delta~{}j(\pi_{1})~{}\alpha\pi_{2}~{}\beta\pi_{3})&\triangleright&\pi_{3}(\beta\leftarrow\pi_{1})\\ (\lambda x~{}\pi~{}t)&\triangleright&\pi(x\leftarrow t)\\ (\delta_{\exists}~{}\langle t,\pi_{1}\rangle~{}\alpha x\pi_{2})&\triangleright&\pi_{2}(x\leftarrow t,\alpha\leftarrow\pi_{1})\\ \end{array}
Definition 4 (Reducibility candidates)

A set R𝑅R of proof-terms is a reducibility candidate if:

  • if πR𝜋𝑅\pi\in R, then π𝜋\pi is strongly normalizable;

  • if α𝛼\alpha is a variable, then αR𝛼𝑅\alpha\in R;

  • if πR𝜋𝑅\pi\in R and ππ𝜋superscript𝜋\pi\triangleright\pi^{\prime}, then πRsuperscript𝜋𝑅\pi^{\prime}\in R;

  • if π𝜋\pi is an elimination and if πRsuperscript𝜋𝑅\pi^{\prime}\in R for all πsuperscript𝜋\pi^{\prime} such that π1πsuperscript1𝜋superscript𝜋\pi\triangleright^{1}\pi^{\prime}, then πR𝜋𝑅\pi\in R.

The set of reducibility candidates is written 𝒞𝒞\mathcal{C}.

Definition 5 (Pre-model)

A pre-model \mathcal{M} (of a given signature) is given by

  • A nonempty set (still) written \mathcal{M} and called the domain of \mathcal{M} (or several domains σsubscript𝜎\mathcal{M}_{\sigma} for many-sorted theories);

  • For each function symbol f𝑓f of arity n𝑛n, a function f:n:superscript𝑓superscript𝑛f^{\mathcal{M}}:\mathcal{M}^{n}\to\mathcal{M};

  • For each predicate symbol p𝑝p of arity n𝑛n, a function p:n𝒞:superscript𝑝superscript𝑛𝒞p^{\mathcal{M}}:\mathcal{M}^{n}\to\mathcal{C}.

If P𝑃P is an atomic formula and ϕitalic-ϕ\phi is a assignment on a premodel \mathcal{M}, the reducibility candidate Pϕ\llbracket P\rrbracket_{\phi} is defined in the obvious way. This definition extends to all formulæ as follows:

  • A proof-term is an element of ABϕ\llbracket A\Rightarrow B\rrbracket_{\phi} if it is strongly normalizable and when it reduces to a proof-term of the form λαπ1𝜆𝛼subscript𝜋1\lambda\alpha~{}\pi_{1}, then for every πsuperscript𝜋\pi^{\prime} in Aϕ\llbracket A\rrbracket_{\phi}, [π/α]π1delimited-[]superscript𝜋𝛼subscript𝜋1[\pi^{\prime}/\alpha]\pi_{1} is an element of Bϕ\llbracket B\rrbracket_{\phi}.

  • A proof-term is an element of ABϕ\llbracket A\land B\rrbracket_{\phi} if it is strongly normalizable and when it reduces to a proof-term of the form π1,π2subscript𝜋1subscript𝜋2\langle\pi_{1},\pi_{2}\rangle, then π1subscript𝜋1\pi_{1} and π2subscript𝜋2\pi_{2} are elements of Aϕ\llbracket A\rrbracket_{\phi} and Bϕ\llbracket B\rrbracket_{\phi}.

  • A proof-term is an element of ABϕ\llbracket A\lor B\rrbracket_{\phi} if it is strongly normalizable and when it reduces to a proof-term of the form i(π1)𝑖subscript𝜋1i(\pi_{1}) (resp. j(π2)𝑗subscript𝜋2j(\pi_{2})) then π1subscript𝜋1\pi_{1} (resp. π2subscript𝜋2\pi_{2}) is an element of Aϕ\llbracket A\rrbracket_{\phi} (resp. Bϕ\llbracket B\rrbracket_{\phi}).

  • A proof-term is an element of ϕ\llbracket\top\rrbracket_{\phi} if it is strongly normalizable.

  • A proof-term is an element of ϕ\llbracket\bot\rrbracket_{\phi} if it is strongly normalizable.

  • A proof-term is an element of xAϕ\llbracket\forall x~{}A\rrbracket_{\phi} if it is strongly normalizable and when it reduces to a proof-term of the form λxπ1𝜆𝑥subscript𝜋1\lambda x~{}\pi_{1} then for every term t𝑡t and every element v𝑣v of \mathcal{M}, [t/x]π1delimited-[]𝑡𝑥subscript𝜋1[t/x]\pi_{1} is an element of Aϕ+x,v\llbracket A\rrbracket_{\phi+\langle x,v\rangle}, where ϕ+x,vitalic-ϕ𝑥𝑣\phi+\langle x,v\rangle is the function that coincides with ϕitalic-ϕ\phi everywhere except on x𝑥x where it takes value v𝑣v.

  • A proof-term is an element of xAϕ\llbracket\exists x~{}A\rrbracket_{\phi} if it is strongly normalizable and when it reduces to a proof-term of the form t,π1𝑡subscript𝜋1\langle t,\pi_{1}\rangle there exists an element v𝑣v of \mathcal{M} such that π1subscript𝜋1\pi_{1} is an element of Aϕ+x,v\llbracket A\rrbracket_{\phi+\langle x,v\rangle}.

A pre-model \mathcal{M} is a pre-model of a congruence \equiv if for all formulæ A𝐴A and B𝐵B such that AB𝐴𝐵A\equiv B, we have Aϕ=Bϕ\llbracket A\rrbracket_{\phi}=\llbracket B\rrbracket_{\phi} for all assignments ϕitalic-ϕ\phi.

The theorem that if a theory has a pre-model then it has the normalization property is proved in two steps. We first check that (1) for each formula A𝐴A and assignment ϕitalic-ϕ\phi, the set Aϕ\llbracket A\rrbracket_{\phi} is a reducibility candidate and then that (2) proofs of A𝐴A are all members of the set Aϕ\llbracket A\rrbracket_{\phi}. The proof of (1) is an induction over the structure of formulæ and the proof of (2) an induction over the structure of proofs. We need to prove, for each deduction rule a lemma such as:

If π1ABϕ\pi_{1}\in\llbracket A\Rightarrow B\rrbracket_{\phi} and π2Aϕ\pi_{2}\in\llbracket A\rrbracket_{\phi}, then (π1π2)Bϕ(\pi_{1}~{}\pi_{2})\in\llbracket B\rrbracket_{\phi}.

Then, as all elements of a reducibility candidate strongly normalize we conclude that all proofs of a formula A𝐴A strongly normalize [2].

2.3 A theory of syntactic constructions

To relativize the pre-model construction of 𝒯𝒯\mathcal{T} w.r.t. a theory 𝒰𝒰\mathcal{U}, we need to express all the syntactic constructions of the proof-language of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U}. The proof-language of 𝒯𝒯\mathcal{T} is complex: it contains proof-variables, proof-terms, as well as the terms of the theory 𝒯𝒯\mathcal{T} (that appear in proof-terms). Moreover, we need to express usual syntactic operations, such as α𝛼\alpha-conversion, substitution, etc.

For that let us consider a language of trees \mathcal{L} generated by a finite number of constructors, that is, an algebra of closed terms generated by a finite number of function symbols written c1,,cNsubscript𝑐1subscript𝑐𝑁c_{1},\ldots,c_{N}—the constructors of \mathcal{L}—whose arities are written k1,,kNsubscript𝑘1subscript𝑘𝑁k_{1},\ldots,k_{N}. In what follows, we assume that the language \mathcal{L} provides two constructors 00 (of arity 00) and s𝑠s (of arity 111) to encode natural numbers.

It is well-known that the latter assumption is sufficient to ensure that all syntactic constructions (such as variables, terms, proof-terms, etc.) can be encoded in \mathcal{L}, by the mean of Gödel numberings. However, the cost of these numberings can be avoided by taking a richer language \mathcal{L}, in which syntactic constructions can be encoding more directly.

Once the language \mathcal{L} has been fixed, the class of all functions that can be defined by primitive recursion on \mathcal{L} is well-defined too.

From the language \mathcal{L}, we build a (mono-sorted) first-order theory 𝒮𝒮\mathcal{S}, which we call the theory of syntactic constructions. This theory is defined as follows:

  1. 1.

    The function symbols of 𝒮𝒮\mathcal{S} are the constructors c1,,cNsubscript𝑐1subscript𝑐𝑁c_{1},\ldots,c_{N} plus, for each primitive recursive definition of a n𝑛nary function on syntactic trees, a function symbol f𝑓f of arity n𝑛n.

  2. 2.

    The only predicate symbol of the theory 𝒮𝒮\mathcal{S} is equality.

  3. 3.

    The axioms of 𝒮𝒮\mathcal{S} are:

    • The equality axioms, that is: reflexivity, symmetry and transitivity of equality, as well as congruence axioms for all function symbols f𝑓f:

      x=xx=yx=zy=zx1=y1xn=ynf(x1,,xn)=f(y1,,yn)𝑥𝑥𝑥𝑦𝑥𝑧𝑦𝑧subscript𝑥1subscript𝑦1subscript𝑥𝑛subscript𝑦𝑛𝑓subscript𝑥1subscript𝑥𝑛𝑓subscript𝑦1subscript𝑦𝑛\begin{array}[]{l}x=x\\ x=y\land x=z\Rightarrow y=z\\ x_{1}=y_{1}\land\cdots\land x_{n}=y_{n}~{}~{}\Rightarrow~{}~{}f(x_{1},\ldots,x_{n})=f(y_{1},\ldots,y_{n})\\ \end{array}
    • Axioms expressing injectivity and non-confusion for constructors:

      ci(x1,,xki)=ci(y1,,yki)x1=y1xki=ykici(x1,,xki)=cj(y1,,ykj)subscript𝑐𝑖subscript𝑥1subscript𝑥subscript𝑘𝑖subscript𝑐𝑖subscript𝑦1subscript𝑦subscript𝑘𝑖subscript𝑥1subscript𝑦1subscript𝑥subscript𝑘𝑖subscript𝑦subscript𝑘𝑖subscript𝑐𝑖subscript𝑥1subscript𝑥subscript𝑘𝑖subscript𝑐𝑗subscript𝑦1subscript𝑦subscript𝑘𝑗bottom\begin{array}[]{r@{~~}c@{~~}l}c_{i}(x_{1},\ldots,x_{k_{i}})=c_{i}(y_{1},\ldots,y_{k_{i}})~{}~{}&\Rightarrow\hfil~{}~{}&x_{1}=y_{1}\land\cdots\land x_{k_{i}}=y_{k_{i}}\\ c_{i}(x_{1},\ldots,x_{k_{i}})=c_{j}(y_{1},\ldots,y_{k_{j}})~{}~{}&\Rightarrow\hfil~{}~{}&\bot\end{array}

      (for all i,j[1..N]i,j\in[1..N] such that ij𝑖𝑗i\neq j).

    • For each primitive recursive definition of a function represented by a function symbol f𝑓f, the axioms expressing its equational theory.

    • For each formula A(x)𝐴𝑥A(x) possibly depending on a variable x𝑥x (as well as other parameters that are left implicit), the induction principle:

      i=1N(x1xkiA(ci(x1,,xki)))xA(x).superscriptsubscript𝑖1𝑁for-allsubscript𝑥1for-allsubscript𝑥subscript𝑘𝑖𝐴subscript𝑐𝑖subscript𝑥1subscript𝑥subscript𝑘𝑖for-all𝑥𝐴𝑥\bigwedge_{i=1}^{N}\Bigl{(}\forall x_{1}~{}\cdots~{}\forall x_{k_{i}}~{}A(c_{i}(x_{1},\ldots,x_{k_{i}}))\Bigr{)}~{}~{}\Rightarrow~{}~{}\forall x~{}A(x)\,.

In what follows, we assume that the usual syntactic structures of 𝒯𝒯\mathcal{T} are represented in the theory 𝒮𝒮\mathcal{S} using the following predicates:

𝑁𝑎𝑡(x)𝑁𝑎𝑡𝑥\mathit{Nat}(x) x𝑥x is a natural number
𝐿𝑒(x,y)𝐿𝑒𝑥𝑦\mathit{Le}(x,y) x𝑥x is less than or equal to y𝑦y
𝑆𝑜𝑟𝑡(x)𝑆𝑜𝑟𝑡𝑥\mathit{Sort}(x) x𝑥x is a sort
𝑇𝑒𝑟𝑚𝑉𝑎𝑟(x,y)𝑇𝑒𝑟𝑚𝑉𝑎𝑟𝑥𝑦\mathit{TermVar}(x,y) x𝑥x is a term variable of sort y𝑦y
𝑇𝑒𝑟𝑚(x,y)𝑇𝑒𝑟𝑚𝑥𝑦\mathit{Term}(x,y) x𝑥x is a term of sort y𝑦y
𝑃𝑟𝑜𝑜𝑓𝑉𝑎𝑟(x)𝑃𝑟𝑜𝑜𝑓𝑉𝑎𝑟𝑥\mathit{ProofVar}(x) x𝑥x is a proof variable
𝑃𝑟𝑜𝑜𝑓(x)𝑃𝑟𝑜𝑜𝑓𝑥\mathit{Proof}(x) x𝑥x is a proof
𝐸𝑙𝑖𝑚(x)𝐸𝑙𝑖𝑚𝑥\mathit{Elim}(x) x𝑥x is a proof that ends with an elimination rule
𝑅𝑒𝑑(x,y)𝑅𝑒𝑑𝑥𝑦\mathit{Red}(x,y) the proof x𝑥x reduces in one step to the proof y𝑦y
𝑅𝑒𝑑𝑛(x,n,y)𝑅𝑒𝑑𝑛𝑥𝑛𝑦\mathit{Redn}(x,n,y) the proof x𝑥x reduces in n𝑛n steps to the proof y𝑦y

Note that all the relations above are primitive recursive.

From these relations, we can define important (and non primitive recursive) relations such as:

𝑅𝑒𝑑(x,y)n(𝑁𝑎𝑡(n)𝑅𝑒𝑑𝑛(x,n,y))𝑆𝑁(x)𝑃𝑟𝑜𝑜𝑓(x)n(𝑁𝑎𝑡(n)y(𝑃𝑟𝑜𝑜𝑓(y)¬𝑅𝑒𝑑𝑛(x,n,y)))superscript𝑅𝑒𝑑𝑥𝑦𝑛𝑁𝑎𝑡𝑛𝑅𝑒𝑑𝑛𝑥𝑛𝑦𝑆𝑁𝑥limit-from𝑃𝑟𝑜𝑜𝑓𝑥missing-subexpressionmissing-subexpression𝑛𝑁𝑎𝑡𝑛for-all𝑦𝑃𝑟𝑜𝑜𝑓𝑦𝑅𝑒𝑑𝑛𝑥𝑛𝑦\begin{array}[]{r@{~~}c@{~~}l}\mathit{Red}^{*}(x,y)~{}~{}&\equiv\hfil~{}~{}&\exists n~{}(\mathit{Nat}(n)\land\mathit{Redn}(x,n,y))\\[6.0pt] \mathit{SN}(x)~{}~{}&\equiv\hfil~{}~{}&\mathit{Proof}(x)~{}\land\\ ~{}~{}&\hfil~{}~{}&\exists n~{}\bigl{(}\mathit{Nat}(n)~{}\land~{}\forall y~{}(\mathit{Proof}(y)\Rightarrow\lnot\mathit{Redn}(x,n,y))\bigr{)}\\ \end{array}

(Intuition: a proof π𝜋\pi is strongly normalizable if there is a number n0𝑛0n\geq 0 such that π𝜋\pi has no n𝑛n-reduct.)

We assume that proof-terms (Def. 2) are represented as trees of \mathcal{L} by the mean of constructors—or constructor aggregates—𝐴𝑥𝑖𝑜𝑚𝐴𝑥𝑖𝑜𝑚\mathit{Axiom} (arity 1), 𝐼𝑚𝑝_I𝐼𝑚𝑝_𝐼\mathit{Imp\_I} (arity 2), 𝐼𝑚𝑝_E𝐼𝑚𝑝_𝐸\mathit{Imp\_E} (arity 2), 𝐴𝑛𝑑_I𝐴𝑛𝑑_𝐼\mathit{And\_I} (arity 2), 𝐴𝑛𝑑_E1𝐴𝑛𝑑_subscript𝐸1\mathit{And\_E}_{1} (arity 1), 𝐴𝑛𝑑_E2𝐴𝑛𝑑_subscript𝐸2\mathit{And\_E}_{2} (arity 1), 𝑂𝑟_I1𝑂𝑟_subscript𝐼1\mathit{Or\_I}_{1} (arity 1), 𝑂𝑟_I2𝑂𝑟_subscript𝐼2\mathit{Or\_I}_{2} (arity 1), 𝑂𝑟_E𝑂𝑟_𝐸\mathit{Or\_E} (arity 5), 𝑇𝑜𝑝_I𝑇𝑜𝑝_𝐼\mathit{Top\_I} (arity 0), 𝐵𝑜𝑡_E𝐵𝑜𝑡_𝐸\mathit{Bot\_E} (arity 1), 𝐹𝑜𝑟𝑎𝑙𝑙_I𝐹𝑜𝑟𝑎𝑙𝑙_𝐼\mathit{Forall\_I} (arity 2), 𝐹𝑜𝑟𝑎𝑙𝑙_E𝐹𝑜𝑟𝑎𝑙𝑙_𝐸\mathit{Forall\_E} (arity 2), 𝐸𝑥𝑖𝑠𝑡𝑠_I𝐸𝑥𝑖𝑠𝑡𝑠_𝐼\mathit{Exists\_I} (arity 2), 𝐸𝑥𝑖𝑠𝑡𝑠_E𝐸𝑥𝑖𝑠𝑡𝑠_𝐸\mathit{Exists\_E} (arity 2) whose name are self-explanatory (see Def. 2 for the correspondence).

Finally, we write 𝑇𝑆𝑢𝑏𝑠𝑡𝑇𝑆𝑢𝑏𝑠𝑡\mathit{TSubst} (resp. 𝑃𝑆𝑢𝑏𝑠𝑡𝑃𝑆𝑢𝑏𝑠𝑡\mathit{PSubst}) the ternary function symbol of 𝒮𝒮\mathcal{S} that computes term-substitution (resp. proof-substitution) inside a proof.

3 An abstract normalization result

We now want to relativize the pre-model construction. Hence, besides the theory 𝒯𝒯\mathcal{T} we want to prove the normalization of, we shall consider another theory 𝒰𝒰\mathcal{U} either in predicate logic or in deduction modulo.

Definition 6

— We say that a theory 𝒰𝒰\mathcal{U} expresses syntactic constructions if it comes with an interpretation (in the sense of Def. 1) of the theory 𝒮𝒮\mathcal{S} (defined in 2.3) into 𝒰𝒰\mathcal{U}, which is structural on terms and formulæ (cf section 1).

From now on, we assume that 𝒰𝒰\mathcal{U} expresses all syntactic constructions, by the mean of an interpretation of the theory 𝒮𝒮\mathcal{S} that we write using ‘\lceil~{}\rceil’ brackets (‘the code of …’). In particular, we write t𝑡\lceil t\rceil the code of any tree t𝑡t\in\mathcal{L}, including (representations of) variables, terms and proof-terms of the theory 𝒯𝒯\mathcal{T}. The sort of 𝒰𝒰\mathcal{U} associated to the unique sort of 𝒮𝒮\mathcal{S} through the interpretation of 𝒮𝒮\mathcal{S} in 𝒰𝒰\mathcal{U} is written \lfloor\mathcal{L}\rfloor, and the corresponding relativisation predicate is written (x)𝑥\lceil\mathcal{L}\rceil(x).

Each primitive recursive relation R𝑅R of arity n𝑛n on \mathcal{L} is expressed in 𝒮𝒮\mathcal{S} as a relation still written R(x1,,xn)𝑅subscript𝑥1subscript𝑥𝑛R(x_{1},\ldots,x_{n}) and defined by

R(x1,,xn)f(x1,,xn)=1,𝑅subscript𝑥1subscript𝑥𝑛𝑓subscript𝑥1subscript𝑥𝑛1R(x_{1},\ldots,x_{n})\quad\equiv\quad f(x_{1},\ldots,x_{n})=1\,,

where f𝑓f is the function symbol of 𝒮𝒮\mathcal{S} associated to the characteristic function of R𝑅R. Via the interpretation \lceil~{}\rceil, the primitive recursive relation R𝑅R is thus represented in 𝒰𝒰\mathcal{U} as a relation written R(x1,,xn)𝑅subscript𝑥1subscript𝑥𝑛\lceil R\rceil(x_{1},\ldots,x_{n}). It is important to notice that this representation is faithful when the theory 𝒰𝒰\mathcal{U} is consistent:

Proposition 2

— If 𝒰𝒰\mathcal{U} is consistent, then for all primitive recursive relations R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) on \mathcal{L} and for all t1,,tnsubscript𝑡1subscript𝑡𝑛t_{1},\ldots,t_{n}\in\mathcal{L} we have:

R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n})  iff  𝒰R(t1,,tn)proves𝒰𝑅subscript𝑡1subscript𝑡𝑛\mathcal{U}\vdash\lceil R\rceil(\lceil t_{1}\rceil,\ldots,\lceil t_{n}\rceil)

In particular, we have: t1=t2subscript𝑡1subscript𝑡2t_{1}=t_{2} iff 𝒰t1=t2proves𝒰subscript𝑡1subscript𝑡2\mathcal{U}\vdash\lceil t_{1}=t_{2}\rceil (for all t1,t2subscript𝑡1subscript𝑡2t_{1},t_{2}\in\mathcal{L}).

Proof

(Direct implication) Assume that R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) holds. From the trace of the computation of the characteristic function f𝑓f of R𝑅R applied to t1,,tnsubscript𝑡1subscript𝑡𝑛t_{1},\ldots,t_{n} we easily build a proof of 𝒮f(t1,,tn)=1proves𝒮𝑓subscript𝑡1subscript𝑡𝑛1\mathcal{S}\vdash f(t_{1},\ldots,t_{n})=1, from which we immediately get a proof of 𝒰R(t1,,tn)proves𝒰𝑅subscript𝑡1subscript𝑡𝑛\mathcal{U}\vdash\lceil R\rceil(\lceil t_{1}\rceil,\ldots,\lceil t_{n}\rceil) through the interpretation of 𝒮𝒮\mathcal{S} in 𝒰𝒰\mathcal{U}.

(Converse implication) Assume that 𝒰R(t1,,tn)proves𝒰𝑅subscript𝑡1subscript𝑡𝑛\mathcal{U}\vdash\lceil R\rceil(\lceil t_{1}\rceil,\ldots,\lceil t_{n}\rceil). We distinguish two cases, depending on whether R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) holds or not.

  • Either R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) holds. In this case we are done.

  • Either R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) does not hold. From the trace of the computation of the characteristic function of R𝑅R, we now get a proof of 𝒮f(t1,,tn)=0proves𝒮𝑓subscript𝑡1subscript𝑡𝑛0\mathcal{S}\vdash f(t_{1},\ldots,t_{n})=0, and thus a proof of 𝒰¬R(t1,,tn)proves𝒰𝑅subscript𝑡1subscript𝑡𝑛\mathcal{U}\vdash\lnot\lceil R\rceil(\lceil t_{1}\rceil,\ldots,\lceil t_{n}\rceil), which is impossible since 𝒰𝒰\mathcal{U} is consistent. Hence this case is absurd.∎

In what follows, we will need a stronger notion of consistency, namely:

Definition 7 (111-consistency)

— We say that 𝒰𝒰\mathcal{U} is 111-consistent if for all primitive recursive relations R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}) on \mathcal{L}, the derivability of

𝒰x1xn((x1)(xn)R(x1,,xn))proves𝒰subscript𝑥1subscript𝑥𝑛subscript𝑥1subscript𝑥𝑛𝑅subscript𝑥1subscript𝑥𝑛\mathcal{U}\vdash\exists x_{1}\cdots\exists x_{n}~{}\bigl{(}\lceil\mathcal{L}\rceil(x_{1})\land\cdots\land\lceil\mathcal{L}\rceil(x_{n})\land\lceil R\rceil(x_{1},\ldots,x_{n})\bigr{)}

entails the existence of trees t1,,tnsubscript𝑡1subscript𝑡𝑛t_{1},\ldots,t_{n}\in\mathcal{L} such that R(t1,,tn)𝑅subscript𝑡1subscript𝑡𝑛R(t_{1},\ldots,t_{n}).

The 111-consistency of a theory entails its consistency, but the converse does not hold in general.

Definition 8 (Realizability translation)

— A realizability translation of a theory 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U} is defined by

  • a function which maps each sort s𝑠s of 𝒯𝒯\mathcal{T} to a sort ssubscript𝑠s_{*} of 𝒰𝒰\mathcal{U} with a relativization predicate s(x)superscript𝑠𝑥s^{*}(x) in 𝒰𝒰\mathcal{U} (with x𝑥x of sort ssubscript𝑠s_{*});

  • a function which maps each variable x𝑥x of sort s𝑠s in 𝒯𝒯\mathcal{T} to a variable xsuperscript𝑥x^{*} of sort ssubscript𝑠s_{*} in 𝒰𝒰\mathcal{U};

  • a function which maps each function symbol f𝑓f of rank s1,,sn,ssubscript𝑠1subscript𝑠𝑛𝑠\langle s_{1},\ldots,s_{n},s\rangle in 𝒯𝒯\mathcal{T} to a term f(z1,,zn)superscript𝑓subscript𝑧1subscript𝑧𝑛f^{*}(z_{1},\ldots,z_{n}) of sort ssubscript𝑠s_{*} in 𝒰𝒰\mathcal{U}, that (possibly) depends on variables z1,,znsubscript𝑧1subscript𝑧𝑛z_{1},\ldots,z_{n} of sort s1,,snsubscript𝑠1subscript𝑠𝑛s_{1*},\ldots,s_{n*}, respectively.

  • a function which maps each predicate symbol p𝑝p of rank s1,,snsubscript𝑠1subscript𝑠𝑛\langle s_{1},\ldots,s_{n}\rangle in 𝒯𝒯\mathcal{T} to a formula of 𝒰𝒰\mathcal{U} written πp(z1,,zn)forces𝜋𝑝subscript𝑧1subscript𝑧𝑛\pi\Vdash p(z_{1},\ldots,z_{n}), that possibly depends on variables π,z1,,zn𝜋subscript𝑧1subscript𝑧𝑛\pi,z_{1},\ldots,z_{n} of sorts ,s1,,snsubscript𝑠1subscript𝑠𝑛\lfloor\mathcal{L}\rfloor,s_{1*},\ldots,s_{n*}, respectively.

Given a realizability translation of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U}, the translation of variables and function symbols is extended to all terms by setting:

(x)=x(f(t1,,tn))f(z1,,zn)(z1t1,,zntn)superscript𝑥superscript𝑥superscript𝑓subscript𝑡1subscript𝑡𝑛superscript𝑓subscript𝑧1subscript𝑧𝑛formulae-sequencesubscript𝑧1subscriptsuperscript𝑡1subscript𝑧𝑛subscriptsuperscript𝑡𝑛\begin{array}[]{l@{~~}c@{~~}l}(x)^{*}\hfil~{}~{}&=\hfil~{}~{}&x^{*}\\ (f(t_{1},\ldots,t_{n}))^{*}\hfil~{}~{}&\equiv\hfil~{}~{}&f^{*}(z_{1},\ldots,z_{n})(z_{1}\leftarrow t^{*}_{1},\ldots,z_{n}\leftarrow t^{*}_{n})\end{array}

Notice that this translation transforms each term t𝑡t of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} into a term tsuperscript𝑡t^{*} of 𝒰𝒰\mathcal{U} whose free variables occur among the variables x1,,xnsubscriptsuperscript𝑥1subscriptsuperscript𝑥𝑛x^{*}_{1},\ldots,x^{*}_{n} of sorts s1,,snsubscript𝑠absent1subscript𝑠absent𝑛s_{*1},\ldots,s_{*n}.

Similarly, we extend the translation of predicate symbols to all formulæ by associating to each formula A𝐴A of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} a formula πAforces𝜋𝐴\pi\Vdash A of 𝒰𝒰\mathcal{U} with free variables π,x1,,xn𝜋subscriptsuperscript𝑥1subscriptsuperscript𝑥𝑛\pi,x^{*}_{1},\ldots,x^{*}_{n} of sorts ,s1,,snsubscript𝑠absent1subscript𝑠absent𝑛\lfloor\mathcal{L}\rfloor,s_{*1},\ldots,s_{*n}. The formula πAforces𝜋𝐴\pi\Vdash A is recursively defined on A𝐴A by the equations:

πp(t1,,tn)(πp(z1,,zn))(z1t1,,zntn)π𝑆𝑁(π)π𝑆𝑁(π)πAB𝑆𝑁(π)απ(𝑅𝑒𝑑(π,𝐼𝑚𝑝_I(α,π))ϕ(ϕA𝑃𝑆𝑢𝑏𝑠𝑡(π,α,ϕ)B))πAB𝑆𝑁(π)π1π2(𝑅𝑒𝑑(p,𝐴𝑛𝑑_I(π1,π2))π1Aπ2B)πAB𝑆𝑁(π)π1(𝑅𝑒𝑑(π,𝑂𝑟_I1(π1))π1A)π2(𝑅𝑒𝑑(π,𝑂𝑟_I2(π2))π2B)πxA(x)𝑆𝑁(π)vπ(𝑅𝑒𝑑(π,𝐹𝑜𝑟𝑎𝑙𝑙_I(v,π))xt(s(x)𝑇𝑒𝑟𝑚(t,s)𝑇𝑆𝑢𝑏𝑠𝑡(π,v,t)A(x)))πxA(x)𝑆𝑁(π)πt(𝑅𝑒𝑑(π,𝐸𝑥𝑖𝑠𝑡𝑠_I(t,π))x(s(x)πA(x)))\begin{array}[]{l@{~}c@{~}l}\pi\Vdash p(t_{1},\ldots,t_{n})\hfil~{}&\equiv\hfil~{}&(\pi\Vdash p(z_{1},\ldots,z_{n}))(z_{1}\leftarrow t^{*}_{1},\ldots,z_{n}\leftarrow t^{*}_{n})\\[6.0pt] \pi\Vdash\top\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)\\[6.0pt] \pi\Vdash\bot\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)\\[6.0pt] \pi\Vdash A\Rightarrow B\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)~{}~{}\land\\ \hfil~{}&\hfil~{}&\forall\alpha~{}\forall\pi^{\prime}~{}(\lceil\mathit{Red}^{*}\rceil(\pi,\lceil\mathit{Imp\_I}\rceil(\alpha,\pi^{\prime}))~{}\Rightarrow\\ \hfil~{}&\hfil~{}&\hphantom{\forall\alpha~{}\forall\pi^{\prime}~{}(}\forall\phi~{}(\phi\Vdash A~{}\Rightarrow~{}\lceil\mathit{PSubst}\rceil(\pi^{\prime},\alpha,\phi)\Vdash B))\\[6.0pt] \pi\Vdash A\land B\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)~{}~{}\land\\ \hfil~{}&\hfil~{}&\forall\pi_{1}\,\forall\pi_{2}~{}(\lceil\mathit{Red}^{*}\rceil(p,\lceil\mathit{And\_I}\rceil(\pi_{1},\pi_{2}))~{}\Rightarrow~{}\pi_{1}\Vdash A~{}{\land}~{}\pi_{2}\Vdash B)\\[6.0pt] \pi\Vdash A\lor B\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)~{}~{}\land\\ \hfil~{}&\hfil~{}&\forall\pi_{1}~{}(\lceil\mathit{Red}^{*}\rceil(\pi,\lceil\mathit{Or\_I}_{1}\rceil(\pi_{1}))~{}\Rightarrow~{}\pi_{1}\Vdash A)~{}\land\\ \hfil~{}&\hfil~{}&\forall\pi_{2}~{}(\lceil\mathit{Red}^{*}\rceil(\pi,\lceil\mathit{Or\_I}_{2}\rceil(\pi_{2}))~{}\Rightarrow~{}\pi_{2}\Vdash B)\\[6.0pt] \pi\Vdash\forall x~{}A(x)\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)~{}~{}\land\\ \hfil~{}&\hfil~{}&\forall v~{}\forall\pi^{\prime}~{}(\lceil\mathit{Red}^{*}\rceil(\pi,\lceil\mathit{Forall\_I}\rceil(v,\pi^{\prime}))~{}\Rightarrow\\ \hfil~{}&\hfil~{}&\hphantom{\forall v~{}\forall\pi^{\prime}~{}(}\forall x^{*}~{}\forall t~{}(s^{*}(x^{*})\land\lceil\mathit{Term}\rceil(t,\lceil s\rceil)~{}\Rightarrow\\ \hfil~{}&\hfil~{}&\hphantom{\forall v~{}\forall\pi^{\prime}~{}(\forall x^{*}~{}\forall t~{}(}\lceil\mathit{TSubst}\rceil(\pi^{\prime},v,t)\Vdash A(x)))\\[6.0pt] \pi\Vdash\exists x~{}A(x)\hfil~{}&\equiv\hfil~{}&\lceil\mathit{SN}\rceil(\pi)~{}~{}\land\\ \hfil~{}&\hfil~{}&\forall\pi^{\prime}~{}\forall t~{}(\lceil\mathit{Red}^{*}\rceil(\pi,\lceil\mathit{Exists\_I}\rceil(t,\pi^{\prime}))~{}\Rightarrow\\ \hfil~{}&\hfil~{}&\hphantom{\forall\pi^{\prime}~{}\forall t~{}(}\exists x^{*}~{}(s^{*}(x^{*})\land\pi^{\prime}\Vdash A(x)))\\[6.0pt] \end{array}

We now need to express in the theory 𝒰𝒰\mathcal{U} that the ‘set’ (in its informal sense) of all proofs π𝜋\pi such that πAforces𝜋𝐴\pi\Vdash A forms a reducibility candidate. Given a formula of 𝒰𝒰\mathcal{U} possibly depending on a variable π𝜋\pi of sort \lfloor\mathcal{L}\rfloor we write

𝐶𝑅π(A(π))π(A(π)𝑃𝑟𝑜𝑜𝑓(π)𝑆𝑁(π))α(𝑃𝑟𝑜𝑜𝑓𝑉𝑎𝑟(α)A(𝐴𝑥𝑖𝑜𝑚(α)))ππ(A(π)𝑅𝑒𝑑(π,π)A(π))π(𝐸𝑙𝑖𝑚(π)π(𝑅𝑒𝑑(π,π)A(π))A(π))subscript𝐶𝑅𝜋𝐴𝜋for-all𝜋𝐴𝜋𝑃𝑟𝑜𝑜𝑓𝜋𝑆𝑁𝜋missing-subexpressionmissing-subexpressionfor-all𝛼𝑃𝑟𝑜𝑜𝑓𝑉𝑎𝑟𝛼𝐴𝐴𝑥𝑖𝑜𝑚𝛼missing-subexpressionmissing-subexpressionfor-all𝜋for-allsuperscript𝜋𝐴𝜋𝑅𝑒𝑑𝜋superscript𝜋𝐴superscript𝜋missing-subexpressionmissing-subexpressionfor-all𝜋𝐸𝑙𝑖𝑚𝜋for-allsuperscript𝜋𝑅𝑒𝑑𝜋superscript𝜋𝐴superscript𝜋𝐴𝜋missing-subexpression\begin{array}[]{r@{\quad}c@{\quad}l@{\quad}l}\mathit{CR}_{\pi}(A(\pi))&\equiv&\forall\pi~{}\bigl{(}A(\pi)~{}\Rightarrow~{}\lceil\mathit{Proof}\rceil(\pi)\land\lceil\mathit{SN}\rceil(\pi)\bigr{)}&\land\\ &&\forall\alpha~{}\bigl{(}\lceil\mathit{ProofVar}\rceil(\alpha)~{}\Rightarrow~{}A(\lceil\mathit{Axiom}\rceil(\alpha))\bigr{)}&\land\\ &&\forall\pi~{}\forall\pi^{\prime}~{}\bigl{(}A(\pi)\land\lceil\mathit{Red}\rceil(\pi,\pi^{\prime})~{}\Rightarrow~{}A(\pi^{\prime})\bigr{)}&\land\\ &&\forall\pi~{}\bigl{(}\lceil\mathit{Elim}\rceil(\pi)\land\forall\pi^{\prime}(\lceil\mathit{Red}\rceil(\pi,\pi^{\prime})\Rightarrow A(\pi^{\prime}))~{}\Rightarrow~{}A(\pi)\bigr{)}\\ \end{array}

We can now introduce the conditions which make that a realizability translation is a realizability interpretation:

Definition 9 (Realizability interpretation)

— A realizability translation of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U} is a realizability interpretation if the following conditions hold:

  1. 1.

    For each sort s𝑠s of 𝒯𝒯\mathcal{T}, we have 𝒰xs(x)proves𝒰𝑥superscript𝑠𝑥\mathcal{U}\vdash\exists x~{}s^{*}(x);

  2. 2.

    For each function symbol f𝑓f of rank s1,,sn,ssubscript𝑠1subscript𝑠𝑛𝑠\langle s_{1},\ldots,s_{n},s\rangle in 𝒯𝒯\mathcal{T}:

    𝒰z1zn(s1(z1)sn(zn)s(f(z1,,zn)))proves𝒰for-allsubscript𝑧1for-allsubscript𝑧𝑛subscriptsuperscript𝑠1subscript𝑧1subscriptsuperscript𝑠𝑛subscript𝑧𝑛superscript𝑠superscript𝑓subscript𝑧1subscript𝑧𝑛\mathcal{U}\vdash\forall z_{1}\cdots\forall z_{n}~{}\bigl{(}s^{*}_{1}(z_{1})\land\cdots\land s^{*}_{n}(z_{n})~{}\Rightarrow~{}s^{*}(f^{*}(z_{1},\ldots,z_{n}))\bigr{)}
  3. 3.

    For each predicate symbol p𝑝p of rank s1,,snsubscript𝑠1subscript𝑠𝑛\langle s_{1},\ldots,s_{n}\rangle in 𝒯𝒯\mathcal{T}:

    𝒰z1zn(s1(z1)sn(zn)𝐶𝑅π(πp(z1,,zn)))proves𝒰for-allsubscript𝑧1for-allsubscript𝑧𝑛subscriptsuperscript𝑠1subscript𝑧1subscriptsuperscript𝑠𝑛subscript𝑧𝑛subscript𝐶𝑅𝜋forces𝜋𝑝subscript𝑧1subscript𝑧𝑛\mathcal{U}\vdash\forall z_{1}\cdots\forall z_{n}~{}\bigl{(}s^{*}_{1}(z_{1})\land\cdots\land s^{*}_{n}(z_{n})~{}\Rightarrow~{}\mathit{CR}_{\pi}(\pi\Vdash p(z_{1},\ldots,z_{n}))\bigr{)}
  4. 4.

    For all pairs of congruent formulæ AA𝐴superscript𝐴A\equiv A^{\prime} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n}:

    𝒰x1xn(s1(x1)sn(xn)π(πAπA))\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})~{}\Rightarrow~{}\forall\pi(\pi\Vdash A~{}\Leftrightarrow~{}\pi\Vdash A^{\prime})\bigr{)}

Items 2 and 3 immediately extend to all terms and formulæ as follows:

Proposition 3 (Typing)

— Given a realizability translation of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U}:

  • For all terms t𝑡t of sort s𝑠s in 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n}:

    𝒰x1xn(s1(x1)sn(xn)s(t))proves𝒰for-allsubscriptsuperscript𝑥1for-allsubscriptsuperscript𝑥𝑛subscriptsuperscript𝑠1subscriptsuperscript𝑥1subscriptsuperscript𝑠𝑛subscriptsuperscript𝑥𝑛superscript𝑠𝑡\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})~{}\Rightarrow~{}s^{*}(t)\bigr{)}
  • For all formulæ A𝐴A of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n}:

    𝒰x1xn(s1(x1)sn(xn)𝐶𝑅π(πA))proves𝒰for-allsubscriptsuperscript𝑥1for-allsubscriptsuperscript𝑥𝑛subscriptsuperscript𝑠1subscriptsuperscript𝑥1subscriptsuperscript𝑠𝑛subscriptsuperscript𝑥𝑛subscript𝐶𝑅𝜋forces𝜋𝐴\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})~{}\Rightarrow~{}\mathit{CR}_{\pi}(\pi\Vdash A)\bigr{)}
Corollary 1 (Normalization of realizers)

— For all formulæ A𝐴A of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n}:

𝒰x1xnπ(s1(x1)sn(xn)πA𝑆𝑁(π))proves𝒰for-allsubscriptsuperscript𝑥1for-allsubscriptsuperscript𝑥𝑛for-all𝜋forcessubscriptsuperscript𝑠1subscriptsuperscript𝑥1subscriptsuperscript𝑠𝑛subscriptsuperscript𝑥𝑛𝜋𝐴𝑆𝑁𝜋\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\forall\pi~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})\land\pi\Vdash A~{}\Rightarrow~{}\lceil\mathit{SN}\rceil(\pi)\bigr{)}

We now extend the realizability relation to sequents as follows: given a sequent A1,,AkBprovessubscript𝐴1subscript𝐴𝑘𝐵A_{1},\ldots,A_{k}\vdash B of 𝒯𝒯\mathcal{T} and a variable π𝜋\pi of sort \lfloor\mathcal{L}\rfloor in 𝒰𝒰\mathcal{U}, we write

π(A1,,AkB)𝐼𝑚𝑝_I(α1,𝐼𝑚𝑝_I(αk,π))A1AkB,\begin{array}[]{l}\pi\Vdash(A_{1},\ldots,A_{k}\vdash B)~{}~{}\equiv\\[3.0pt] \quad\lceil\mathit{Imp\_I}\rceil(\lceil\alpha_{1}\rceil,\cdots\lceil\mathit{Imp\_I}\rceil(\lceil\alpha_{k}\rceil,\pi)\cdots)\Vdash A_{1}\Rightarrow\cdots\Rightarrow A_{k}\Rightarrow B\,,\\ \end{array}

where α1,,αksubscript𝛼1subscript𝛼𝑘\alpha_{1},\ldots,\alpha_{k} are pairwise distinct proof-variables (of 𝒯𝒯\mathcal{T}) that represent the assumptions A1,,Aksubscript𝐴1subscript𝐴𝑘A_{1},\ldots,A_{k}. Corollary 1 immediately extends to sequent realizers:

Corollary 2

— For all sequents ΓAprovesΓ𝐴\Gamma\vdash A of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n}:

𝒰x1xnπ(s1(x1)sn(xn)π(ΓA)𝑆𝑁(π))\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\forall\pi~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{n}(x^{*}_{n})\land\pi\Vdash(\Gamma\vdash A)~{}\Rightarrow~{}\lceil\mathit{SN}\rceil(\pi)\bigr{)}
Proposition 4 (Existence of a realizer)

— Let (_)superscript_(\_)^{*} be a realizability interpretation of 𝒯𝒯\mathcal{T} in 𝒰𝒰\mathcal{U}. If a sequent A1,,AkBprovessubscript𝐴1subscript𝐴𝑘𝐵A_{1},\ldots,A_{k}\vdash B of 𝒯𝒯\mathcal{T} with free variables x1,,xnsubscript𝑥1subscript𝑥𝑛x_{1},\ldots,x_{n} of sorts s1,,snsubscript𝑠1subscript𝑠𝑛s_{1},\ldots,s_{n} has a proof π𝜋\pi in intuitionistic deduction modulo 𝒯𝒯\mathcal{T} with free proof-variables α1:A1:subscript𝛼1subscript𝐴1\alpha_{1}:A_{1}, …, αk:Ak:subscript𝛼𝑘subscript𝐴𝑘\alpha_{k}:A_{k}, then

𝒰x1xn(s1(x1)sk(xn)π(A1,,AkB))\begin{array}[]{rcl}\mathcal{U}&\vdash&\forall x^{*}_{1}\cdots\forall x^{*}_{n}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{k}(x^{*}_{n})~{}\Rightarrow~{}\lceil\pi\rceil\Vdash(A_{1},\ldots,A_{k}\vdash B)\bigr{)}\end{array}
Proof

By induction on the derivation of π:(A1,,AnB)\pi:(A_{1},\ldots,A_{n}\vdash B).

Theorem 3.1

— If a theory 𝒯𝒯\mathcal{T} has a realizability interpretation in 𝒰𝒰\mathcal{U} and if 𝒰𝒰\mathcal{U} is 111-consistent, then 𝒯𝒯\mathcal{T} enjoys the strong normalization property.

Proof

Assume π𝜋\pi is a proof of A1,,AnBprovessubscript𝐴1subscript𝐴𝑛𝐵A_{1},\ldots,A_{n}\vdash B (in intuitionistic deduction modulo 𝒯𝒯\mathcal{T}). From Prop. 4 we get

𝒰x1xk(s1(x1)sk(xk)π(A1,,AnB)),\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{k}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{k}(x^{*}_{k})~{}\Rightarrow~{}\lceil\pi\rceil\Vdash(A_{1},\ldots,A_{n}\vdash B)\bigr{)}\,,

hence

𝒰x1xk(s1(x1)sk(xk)𝑆𝑁(π))proves𝒰for-allsubscriptsuperscript𝑥1for-allsubscriptsuperscript𝑥𝑘subscriptsuperscript𝑠1subscriptsuperscript𝑥1subscriptsuperscript𝑠𝑘subscriptsuperscript𝑥𝑘𝑆𝑁𝜋\mathcal{U}\vdash\forall x^{*}_{1}\cdots\forall x^{*}_{k}~{}\bigl{(}s^{*}_{1}(x^{*}_{1})\land\cdots\land s^{*}_{k}(x^{*}_{k})\Rightarrow\lceil\mathit{SN}\rceil(\lceil\pi\rceil)\bigr{)}

using Cor. 2, and finally

𝒰SN(π),proves𝒰𝑆𝑁𝜋\mathcal{U}\vdash\lceil SN\rceil(\lceil\pi\rceil)\,,

from the fact that all domains of interpretation of sorts are inhabited. The latter means that

𝒰𝑃𝑟𝑜𝑜𝑓(π)n(𝑁𝑎𝑡(n)R(x,n)),proves𝒰𝑃𝑟𝑜𝑜𝑓𝜋𝑛𝑁𝑎𝑡𝑛𝑅𝑥𝑛\mathcal{U}\vdash\lceil\mathit{Proof}\rceil(\lceil\pi\rceil)~{}\land~{}\exists n~{}(\lceil\mathit{Nat}\rceil(n)\land\lceil R\rceil(x,n))\,,

writing

R(x,n)y(𝑃𝑟𝑜𝑜𝑓(y)¬𝑅𝑒𝑑𝑛(x,n,y))𝑅𝑥𝑛for-all𝑦𝑃𝑟𝑜𝑜𝑓𝑦𝑅𝑒𝑑𝑛𝑥𝑛𝑦R(x,n)~{}~{}\equiv~{}~{}\forall y~{}(\mathit{Proof}(y)\Rightarrow\lnot\mathit{Redn}(x,n,y))

the relation of 𝒮𝒮\mathcal{S} which expresses that x𝑥x has no n𝑛n-reduct. But since this relation is primitive recursive, and since 𝒰𝒰\mathcal{U} is 111-consistent, we deduce that there exists a natural number n𝑛n such that π𝜋\pi has no n𝑛n-reduct. Which means that π𝜋\pi is strongly normalizable.∎

References

  • [1] G. Dowek, Th. Hardin, and C. Kirchner. Theorem proving modulo. Journal of Automated Reasoning, 31:33–72, 2003.
  • [2] G. Dowek and B. Werner. Proof normalization modulo. The Journal of Symbolic Logic, 68(4):1289–1316, 2003.